Effects of Violation of Equivalence Principle on UHE Neutrinos at IceCube in 4 Flavour Scenario - Madhurima Pandey (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
If weak equivalence principle is violated then different types of neutrinos would couple differently with gravity and that may produce a gravity induced oscillation for the neutrinos of different flavour. We explore here the possibility that very small violation of the principle of weak equivalence (VEP) can be probed by ultra high energy neutrinos from distant astrophysical sources. The very long baseline length and the ultra high energies of such neutrinos could be helpful to probe very small VEP. We consider a 4-flavour neutrino scenario (3 active + 1 sterile) with both mass-flavour and gravity induced oscillations and compare the detection signatures for these neutrinos (muon tracks and shower events) with and without gravity induced oscillations at a kilometer scale detector such as IceCube. We find that even very small VEP (∼ 10−42) can considerably affect the detected muon yield produced by UHE neutrinos from distant Gamma Ray Bursts (GRBs).